Streams, walls, and feeds 109 design guidelines for improving notifications, messages, and alerts sent through social networks and RSS - Estes, Janelle; Schade, Amy.; Nielsen, Jakob, 1957-; Safari eBooks (Fremont, Calif. : Nielsen Norman Group, 2010)
"This report conducted by the Nielsen Norman Group is based on empirical observations of actual user behavior, as people accessed messages and postings from more than 120 companies, government agencies, and non-profit organizations on Twitter, Facebook, MySpace, and LinkedIn, as well as these organizations' RSS feeds. Most of this research was conducted in the United States, with a smaller number of users studied in the U.K. and Australia"--Resource description page.
Description based on resource description page (viewed May 24, 2010).
Keywords: Online social networks; RSS feeds; Marketing research; Electronic books